Legal Policy in Handling Domestic Violence The Role of Protection and Legal Institutions - Purbowati, Lindri; Redi, Ahmad (Green Publisher Indonesia, 2024)
Domestic violence (DV) is a complex phenomenon that stems from various social, cultural and economic aspects. Domestic violence includes not only physical violence but also psychological, sexual, and economic violence, all of which have a significant impact on victims and their families. The Indonesian government has issued various regulations and laws to combat domestic violence, such as Law No. 23/2004 on the Elimination of Domestic Violence. This research aims to analyze the effectiveness of legal policies to combat domestic violence (KDRT) in Indonesia as well as the role of protection organizations and law enforcement agencies in providing support to victims. Domestic violence is a serious problem that requires comprehensive and systematic treatment. This research uses qualitative methods with analysis of policy documents, annual reports and statistics on domestic violence cases. The research results show that although there are supportive policies, their implementation is still not optimal due to lack of coordination between institutions, lack of resources and sensitivity of the judicial apparatus to domestic violence issues. Protection agencies play an important role in assisting and assisting victims, but limited financial and human resources hamper the effectiveness of these agencies. The study recommends increased training for law enforcement officers, increased funding for protection agencies as well as public education campaigns to increase awareness and participation in managing family violence. Collaboration between the government, protection agencies, law enforcement and the community is very important in creating a more effective and fair system for dealing with family violence.